You are on page 1of 18

Introductory Mathematics II (MTS 102

)
Integration
Dansu, Emmanuel Jesuyon
Department of Mathematical Sciences
Federal University of Technology, Akure
ejdansu@futa.edu.ng

1 Basic Principles of Integration
1.1 Integration as Summation
Integration can be regarded as a process of adding up, that is, as a summation. Whenever we wish to
find areas under curves, volumes etc, we can do this by finding the area or volume of a small portion,
and then summing over the whole region of interest. The calculation can then be performed using the
technique of definite integration. Integration as a sum can be expressed as
Z b b
X
f (x)dx = lim f (x)δx (1.1)
a δx→0
x=a

1.1.1 Examples
R6 3
1. limδx→0 x=6 3
P
x=1 4x δx = 1 4x dx
R3 2
2. limδx→0 x=3 2
P
x=−2 (x + sin x) δx = −2 (x + sin x) dx

1.2 Integration as Anti-Differentiation
1.2.1 Example
Given the function y = 4x2 + 5x + 7. From our knowledge of differentiation, we proceed as follows

dy d
= (4x2 + 5x + 7) (1.2)
dx dx
dy
= 8x + 5 (1.3)
dx
If we turn around to integrate, though the general concept has not been introduced, we have
dy = (8x + 5)dx (1.4)
Z Z
dy = (8x + 5)dx
8x2 5x1
Z
dy = +
2 1
2
y = 4x + 5x (1.5)

1

1. whenever we integrate. The arbitrary constant cancels out in the process of substituting a and b. 1. we will obtain c = 7 and then we would have y = 4x2 + 5x + 7 as given initially. An indefinite integral can be expressed as Z f (x)dx = F (x) + c (1.5). For instance. an arbitrary constant is added to the result to compensate for any likely missing constant. given dy = (8x + 5)dx and y(0) = 7. A definite integral can be expressed as Z b f (x)dx = F (b) − F (a) (1.7) where f (x) is the integrand. we see that we have a function looking almost like the initial function y = 4x2 + 5x + 7. as the case may be.4. for dy = (8x + 5)dx.6) a where F (a) and F (b) are the values of the integral of f (x) evaluated at the integral limits a and b.4 Definite and Indefinite Integral An integral is the result of integration while an integrand is the function to be integrated. x2 Z x dx = +c (1. F (x) is the integral and c is the arbitrary constant. it is obvious that integration is a process of anti-differentiation. As such.8) 2 2. 1 1 x2 Z  x dx = +c (1. more information would be required. 1.From the result. The result of a definite integral is usually a numerical value while the result of an indefinite integral is a function with an arbitrary or actual constant. a more comprehensive result would be y = 4x2 + 5x + c. As a result of that. where c is the arbitrary constant.3 Arbitrary Constant From (1. So. every constant value goes to 0. In order to get the actual constant.9) −2 2  2 −2  (−2)2  (1) = − 2 2 1 4 = − 2 2 3 = − (1.10) 2 2 . we discover that the 7 in the initial function is missing. Each time differentiation is done.1 Examples 1.

2 Integration of Polynomials Given a general polynomial of the form y = axn . we have Z Z ydx = axn dx (2. x2 dx R 3. we have 3 .4) 4 2.1) axn+1 = +c (2. x3+1 3x2+1 4x1+1 6x0+1 Z (x3 + 3x2 − 4x + 6)dx = + − + +c (2. (6x5 + 5x4 − 4x3 + 3x2 − 2x + 1)dx R  2x7 −3x5 +x4  2.2) n+1 2.3) 3+1 2+1 1+1 0+1 x4 3x3 4x2 6x1 = + − + +c 4 3 2 1 1 4 = x + x3 − 2x2 + 6x + c (2.1 Examples 1. x4 − 3x3 + x2 x4 3x3 x2 Z   Z   dx = − + dx (2.6) 4 2 2.2 Exercise Evaluate the following: R 1. (x2 + x + 1)(3x2 − 2x + 1)dx f 0 (x) 3 Integration of Functions of the Form f (x) 1 R In trying to evaluate x dx using the previous method.5) x x x x Z x3 − 3x2 + x dx  = x4 3x3 x2 = − + +c 4 3 2 1 4 1 = x − x3 + x2 + c (2.

8) 2x + 3x − 1 x+1 d R 2.1 Examples 4x+3 d R 1. we see that d 1 (ln x) = (3.3) dx x following the principle that d f 0 (x) [ln f (x)] = . thinking of integration as anti- differentiation. Given x2 +2x+1 dx. f 0 (x) Z dx = ln f (x) + c (3.5) Z x Z 1 dx = d(ln x) x = ln x + c (3. To evaluate 2x2 +3x−1 dx. since it is clear that dx (2x2 + 3x − 1) = 4x + 3. it is obvious that x dx = ln x + c.4) dx f (x) d Since dx (ln x) = x1 . we have that dx (x2 + 2x + 1) = 2x + 2 = 2(x + 1). However. (3.7) f (x) 3. Z Z 1 dx = x−1 dx (3. On a general note.2) The method is not helpful because the result is undefined. we can have 1 dx = d(ln x) (3.6) 1 R So. so we proceed as follows 4 .1) x x−1+1 = +c −1 + 1 x0 = +c 0 1 = +c 0 = ∞ (3. then Z 4x + 3 2 dx = ln(2x2 + 3x − 1) + c (3.

1 × (x + 1) Z Z x+1 2 dx = dx (3. x3 +3x 2 −3x+5 dx R 2x 3. sec tan x dx 4 Integration of Trigonometric Functions 4. (4.1) 2. For instance Z sin xdx = − cos x + c.2 Exercise Evaluate the following 2 +2x+5 1.1 Examples Integration of simple trigonometric functions is easily understood from the perspective of anti-differentiation. (4.3) cos x 1 × sin x Z = dx cos x −1 × −1 × sin x Z = dx cos x − sin x Z = − dx cos x = − ln cos x + c.9) x + 2x + 1 x2 + 2x + 1 Z 1 2 × 2 × (x + 1) = dx x2 + 2x + 1 Z 1 2(x + 1) = 2 dx 2 x + 2x + 1 Z 1 2x + 2 = dx 2 x2 + 2x + 1 1 = ln(x2 + 2x + 1) + c (3. 1. we have Z Z sin x tan xdx = dx (4.2) R 3.10) 2 3. (4. To evaluate tan xdx. Also Z cos xdx = sin x + c.4) 5 . 7x21x R 3 +x2 +5x+8 dx R x2 +2x−1 2.

12) 2 2 We need one of the relationships above to evaluate Z sin 2x cos xdx From inspection.10) 2 2     p+q p−q cos p + cos q = 2 cos cos (4. How? From (4.To evaluate Z sin2 xdx we have to use our knowledge of trigonometry since there is no direct solution.7) 2 2 Z Z 1 1 = dx − cos 2xdx 2 2 1 1 1 = x − × sin 2x + c 2 2 2 1 1 = x − sin 2x + c (4.6) 2 2 Now.9) 2 2     p+q p−q sin p − sin q = 2 cos sin (4. we can have     p+q p−q 1 sin cos = (sin p + sin q) (4.9). We have to recall that cos 2x = cos(x + x) (4.14) 2 2 2 2 6 .8) 2 4 Recall that     p+q p−q sin p + sin q = 2 sin cos (4. we perform the integration.11) 2 2     p+q p−q cos p − cos q = −2 sin sin (4. Z Z   2 1 1 sin xdx = − cos 2x dx (4.13) 2 2 2     p+q p−q 1 1 sin cos = sin p + sin q (4.9) will do the job.5) cos 2x cos x cos x − sin x sin x = cos 2x cos2 x − sin2 x = cos 2x (1 − sin2 x) − sin2 x = cos 2x 1 − sin2 x − sin2 x = cos 2x 1 − 2 sin2 x = 2 sin2 x 1 − cos 2x = 1 − cos 2x sin2 x = 2 1 1 sin2 x = − cos 2x (4. it looks like (4.

cos 7z sin 4zdz 5 Integration by Substitution Sometimes. 7 . Such substitutions can be algebraic or trigonometric.15) and (4.17) 2 2 We can now proceed with the solution as follows Z Z   1 1 sin 2x cos xdx = sin 3x + sin x dx (4. we have p = 3x. sec xdx R 3. cot wdw R 2. cos 5y sin 3ydy R 6.18) 2 2 Z Z 1 1 = sin 3xdx + sin xdx 2 2   1 1 1 = × − cos 3x + (− cos x) + c 2 3 2 1 1 = − cos 3x − cos x + c (4.16) simulataneously.2 Exercise Evaluate the following: R 1. cosec ydy R 5. we will have to make substitutions. On the other hand. cos2 xdx R 4. in order to integrate certain functions.15) 2 p−q =x (4.Comparing the Left Hand Side with sin 2x cos x. q=x and 1 1 sin 2x cos x = sin 3x + sin x (4.16) 2 Solving (4. an alphabet is replaced with a trigonometric ratio when we perform trigonometric substitution. we replace an expression with an alphabet.19) 6 2 4. have p+q = 2x (4. In algebraic subsitution.

5. we can progress as follows 8 √ 42     p−2 √ Z Z dp x 5x + 2 dx = p (5.1 Algebraic Substitution 5. at x = 1.4) 8 . Note should be taken that the integral limits will also change as follows: Since p = 5x + 2.2) 63 To evaluate 8 √ Z x 5x + 2 dx 1 p−2 dp let p = 5x + 2 so x = 5 and = 5 =⇒ dx = dp dx 5 . Z Z 6 dp (9x + 2) dx = p6 (5. Now.1 Examples To evaluate Z (9x + 2)6 dx we can take p = 9x + 2 such that dp =9 dx dp and dx = 9 .1. p = 7 and at x = 8. p = 42.3) 1 7 5 5 Z 42 1 1 = (p − 2)p 2 dp 25 7 Z 42  1 3 1  = p 2 − 2p 2 dp 25 7 Z 42 Z 42  1 3 1 = p 2 dp − 2 p 2 dp 25 7 7 " # " 3 #42  5 42 1  p2 p2 = 5 −2 3  25 2 2 7 7 " #42  5 # 42 " 3 1  2p 2 2p 2 = −2  25 5 3 7 7  h i  1 2 5 42 4 3 h i 42 = p2 − p2 25 5 7 3 7 2 h 5 5 i 4 h 3 3 i = 42 − 7 − 2 2 42 − 7 2 2 125 75 = 167. So.3090 (5.1) 9 Z 1 = p6 dp 9 1 p7   = +c 9 7 1 7 = p +c 63 1 = (9x + 2)7 + c (5.

2 Exercise Evaluate the following: Rp 1. cos 15 q dq √ 1 R (1+ x) 3 9. x(6x − 1)5 dx R √ 3. p3 ep dp R sin q 8.5) cos x Z = p6 dp  7 p = +c 7 1 7 = p +c 7 1 = (sin x)7 + c 7 1 7 = sin x + c (5.1.{The reference triangles will be discussed in the class} 9 . These substitutions are obtained from the reference right-angled triangles for the three basic substitutions identifying the sides labelled x and a for each substitution. a2 + x2 . and x = a sec θ for transforming integrals involving a2 − x2 . √ x dx 5. (w + 5) 3 dw R 5. x = a tan θ. y 4y + 9 dy R 1 4.To evaluate Z sin6 x cos xdx dp dp let p = sinx =⇒ dx = cos x =⇒ dx = cos x and so Z Z 6 dp sin x cos xdx = p6 × cos x × (5.6) 7 5.2 Trigonometric Substitution The most √ common substitutions √ are √ x = a sin θ. and x2 − a2 into integrals we can evaluate directly. tan2 x sec2 xdx R 4 7. sin x cos9 xdx R 6. (2x + 3)7 dx R 2.

We also have to transform the limits of integration using x = 3 sin θ: At x = 0.10) 10 . At x = 23 . x2 (2 tan θ)2 Z Z dx = × 2 sec2 θdθ (5. Z 3 Z π 2 dx 6 3 cos θdθ √ = p (5. So.2.8) 6 To evaluate x2 Z dx 4 + x2 then x = 2 tan θ → dx = 2 sec2 θdθ. θ = π6 .9) 4 + x2 4 + (2 tan θ) 2 4 tan2 θ Z = 2 × 2 sec2 θdθ 4 + 4 tan θ 4 tan2 θ Z = 2 × 2 sec2 θdθ 4(1 + tan θ) 4 tan2 θ Z = × 2 sec2 θdθ 4 sec2 θ Z = 2 tan2 θdθ (5.5. Now.1 Examples Considering Z 3 2dx √ 0 9 − x2 we make the substitution x = 3 sin θ → dx = 3 cos θdθ.7) 0 9 − x2 0 9 − (3 sin θ)2 Z π 6 3 cos θdθ = p 0 9 − 9 sin2 θ Z π 6 3 cos θdθ = p 0 9(1 − sin2 θ) Z π 6 3 cos θdθ = √ 0 9 cos2 θ Z π 6 3 cos θdθ = 0 3 cos θ Z π 6 = dθ 0 π = [θ]06 π = −0 6 π = (5. θ = 0.

zz2 −1 R v2 dv 4.2) dx dx dx Multiplying through by dx. = v(x).11) Z Z  2 = 2 sec θdθ − dθ = 2(tan θ − θ) + c = 2 tan θ − 2θ + c (5.3) Z Z Z dy = udv + vdu Z Z y = udv + vdu Z Z uv = udv + vdu Z Z udv = uv − vdu (6. 0 a2 − x2 dx R dy 2. In such cases. The formula for integration by parts arises from the Product Rule technique in differential calculus as follows: Given y = uv (6. 2 5 (1−v ) 2 √ t2 −49 R 5. we can integrate by parts as we will soon find out. 3+y 2 R 3 dz 3. dy dv du =u +v (6. 1 − 9r2 dr 6 Integration by Parts Occasions arise when we have to integrate the product of two functions and the techniques we have learnt so far may not be applicable.12) 5.1) where y = y(x).2 Exercise Evaluate the following: Ra√ 1. t dt R2 dx 6.4) 11 .2. 0 8+2x2 R√ 7. u = u(x). we can progress as follows dy = udv + vdu (6. Z Z 2 2 tan θdθ = 2 (sec2 θ − 1)dθ (5.

which should be integrable.1 Examples In order to evaluate Z I= x2 sin xdx we take u = x2 → du = 2xdx and dv = sin xdx → v = − cos x + c and Z I = uv − vdu Z 2 I = x (− cos x) − (− cos x) × 2xdx Z 2 I = −x cos x + 2 x cos xdx I = −x2 cos x + 2I1 (6. 6. Considering Z I= e2x cos xdx it is not very clear the choices of u and dv to make but we can make a try with u = e2x → du = 2e2x dx and dv = cos xdx → v = sin x + c and then 12 . dv and obtaining du and v.7) where d = 2c is the arbitrary constant. we have to identify a part of the function u.5). To integrate by parts.4) is the required formula for the integration of functions by parts. The process continues until part integration is no longer necessary. we have I = −x2 cos x + 2(x sin x + cos x + c) I = −x2 cos x + 2x sin x + 2 cos x + 2c I = −x2 cos x + 2x sin x + 2 cos x + d (6. we repeat the process by taking u = x → du = dx and dv = cos xdx → v = sin x + c and then Z I1 = uv − vdu Z I1 = x sin x − sin xdx I1 = x sin x − (− cos x) + c I1 = x sin x + cos x + c (6.6) Substituting (6. After identifying u.Equation (6.6) into (6.5) Since Z I1 = x cos xdx cannot be integrated directly. we substitute using the formula. which should be more easily differentiable (and probably goes to a constant after a degree of differentiation) than the second part dv.

9) R The loop should be ending but fortunately we can capitalize on the fact that I = e2x cos xdx appears in (6.10) 5 5 It is a bit tricky to evaluate Z tan−1 xdx Since it is difficult to integrate tan−1 x. so Z I1 = uv − vdu Z I1 = e (− cos x) − (− cos x) × 2e2x dx 2x Z I1 = −e cos x + 2 e2x cos xdx 2x I1 = −e2x cos x + 2I (6. Z I = uv − vdu Z −1 1 I = tan x × x − x × dx 1 + x2 Z x I = x tan−1 x − dx 1 + x2 Z −1 1 2x I = x tan x − dx 2 1 + x2 1 I = x tan−1 x − ln(1 + x2 ) + c (6.11) 2 13 . So we substitute (6. So. we take u = tan−1 x → du = 1+x 1 2 dx and dv = dx → v = x + c.9) into (6.9). Z I = uv − vdu Z I = e sin x − sin x × 2e2x dx 2x Z I = e sin x − 2 e2x sin xdx 2x I = e2x sin x − 2I1 (6.8) and obtain the result as follows I e2x sin x − 2I1 = I e2x sin x − 2(−e2x cos x + 2I) + c = I e2x sin x + 2e2x cos x − 4I + c = I + 4I e2x sin x + 2e2x cos x + c = 5I e2x sin x + 2e2x cos x + c = 1 2x 2 1 I = e sin x + e2x cos x + c 5 5 5 1 2x 2 2x I = e sin x + e cos x + d (6.8) For Z I1 = e2x sin xdx we take u = e2x → du = 2e2x dx and dv = sin x → v = − cos x + c.

when b = 0. In such cases. u3 sin udu R √ 3. ln vdv 4.3) b +b b b+1 14 . we have to resolve the compound fractions into partial fractions for easy integration.2) From equation (7.1) b +b b(b + 1) b+4 A B ≡ + b(b + 1) b b+1 b + 4 = A(b + 1) + Bb (7.1 Examples 7. sin−1 wdw R R 3 5. Compound fractions are classified based on their denominators. 7. e−3t sin 5tdt R R 2. A = 4. x 4 ln 4xdx 6. B = −3 and so b+4 4 3 2 = − (7. when b = −1.6.1 Compound Fractions with Denominators involving Nonrepeated Linear Factors To evaluate Z 1 b+4 db 1 2 b2 + b b+4 we resolve b2 +b into partial fractions as follows: b+4 b+4 2 = (7.2 Exercise Evaluate the following: 1. ln 23 z cos 12 zdz R 7 Integration of Compound Fractions There are times when we have to integrate compound fractions.2).1. cos−1 2ydy R 7.

Now.4) 1 b2 + b 1 b b+1 2 2 Z 1 Z 1 4 3 = db − db 1 b 1 b + 1 2 2 = 4 (ln |b|)11 − 3 (ln |b + 1|)11 2 2 . we proceed to solve the problem Z 1 Z 1  b+4 4 3 db = − db (7.

.

.

 .

.

1.

.

.

1 .

= 4 ln .

1 − .

− 3 ln .

(1 + 1) − .

.

+ 1 .

.

2 2 .

.

.

.

.

1 .

.

3 .

= 4 ln .

.

1 − .

.

− 3 ln .

.

2 − .

.

8) 6A + 2C = −1 (7. 2 2 1 1 = 4 ln − 3 ln 2 2 1 = ln 2 = − ln 2 = −0.2 Compound Fractions with Denominators involving Repeated Linear Factors To evaluate Z dc (c2 − 1)2 1 we resolve (c2 −1)2 into partial fractions. that is 1 1 = (7. we obtain the following simultaneous equations in A and C: 2A − 2C = −1 (7.7).6931 (7. When we substitute c = 0 and c = 2 together with the values of B and D.9) Solving the simulatneous equations.1.6) (c2 − 1)2 [(c − 1)(c + 1)]2 1 1 = (c2 − 1)2 (c − 1)2 (c + 1)2 1 A B C D ≡ + + + (c − 1)2 (c + 1)2 c − 1 (c − 1)2 c + 1 (c + 1)2 1 = A(c − 1)(c + 1)2 + B(c + 1)2 + C(c − 1)2 (c + 1) + D(c − 1)2 (7. when c = 1. it is clear that 1 1 1 1 1 =− + + + (7. B = 41 . So. when c = −1. we have that A = − 41 and C = 14 .7) From equation (7.5) 7. D = 41 .10) (c2 − 1)2 4(c − 1) 4(c − 1)2 4(c + 1) 4(c + 1)2 We now proceed to integrate as follows 15 .

B and D.20) 4 4 2 7.4 Improper Compound Fractions To evaluate 3g 3 − g 2 − 13g − 13 Z dg g2 − g − 6 3 2 we have to resolve 3g −g −13g−13 g 2 −g−6 into partial fractions but the fraction is improper so we have to evaluate to identify the whole and the fraction parts.1.18) f4 − 1 4(f − 1) 4(f + 1) 2(f 2 + 1) Z Z Z 1 1 1 1 1 1 = df − df + df (7. Then f2 1 1 1 4 = − + 2 (7.14) f4 − 1 (f − 1)(f + 1)(f 2 + 1) f2 A B Cf + D = + + 2 (7. we have that 16 .11) (c − 1)2 2 4(c − 1) 4(c − 1)2 4(c + 1) 4(c + 1)2 Z Z Z Z 1 1 1 1 1 1 1 1 = − dc + 2 dc + dc + dc 4 c−1 4 (c − 1) 4 (c + 1) 4 (c + 1)2 1 1 1 1 = − ln |c − 1| − + ln |c + 1| − +c (7.16) From equation (7. When we substitute f = 0 together with the values of A and B.1. we get C = 0. B = − 14 . On evaluation. Z Z   1 1 1 1 1 dc = − + + + dc (7. When we substitute f = 2 and the values of A. when f = −1.3 Compound Fractions with Denominators involving Irreducible Quadratic Factors To evaluate f2 Z df f4 − 1 f2 we resolve f 4 −1 into partial fractions. A = 41 . we obtain D = 21 . f2 f2 = (7.12) 4 4(c − 1) 4 4(c + 1) 7. when f = 1.15) (f − 1)(f + 1)(f 2 + 1) f −1 f +1 f +1 f2 = A(f + 1)(f + 1) + B(f − 1)(f 2 + 1) + (Cf + D)(f − 1)(f + 1) 2 (7.13) f4 − 1 (f 2 − 1)(f 2 + 1) f2 f2 = (7.16).17) f −1 4(f − 1) 4(f + 1) 2(f + 1) The integration goes as follows f2 Z Z   1 1 1 df = − + df (7.19) 4 f −1 4 f +1 2 f2 + 1 1 1 1 = ln |f − 1| − ln |f + 1| + tan−1 f + c (7.

24) From equation (7.2 Exercise Evaluate the following: 1.30) 2 7. 7g − 1 7g − 1 = (7.23) (g + 2)(g − 3) g+2 g−3 7g − 1 = A(g − 3) + B(g + 2) (7.24).28) g+2 g−3  2 g = 3 + 2g + 3 ln |g + 2| + 4 ln |g − 3| + c (7. So. 1 t3 +t dt 17 . (z+1)(z−2)3 dz R √3 3t2 +t+4 7. 2uu+3 R 3 −8u du x2 dx R 4. when g = 3. p2 −7p+12 dp 3.22) g2 −g−6 (g + 2)(g − 3) 7g − 1 A B ≡ + (7.27) g2 − g − 6 g+2 g−3 Z Z Z Z 1 1 = 3 gdg + 2 dg + 3 dg + 4 dg (7.25) g2 −g−6 g+2 g−3 And equation (7.21) g −g−6 g −g−6 7g−1 We now have to resolve g 2 −g−6 into partial fractions.21) becomes 3g 3 − g 2 − 13g − 13 3 4 2 = (3g + 2) + + (7. t3 +tdt2 −2t R R 2p+1 2. B = 4.26) g −g−6 g+2 g−3 Therefore 3g 3 − g 2 − 13g − 13 Z Z   3 4 dg = 3g + 2 + + dg (7.29) 2 3 2 = g + 2g + 3 ln |g + 2| + 4 ln |g − 3| + c (7. A = 3. 7g − 1 3 4 = + (7. when g = −2. (x−1)(x 2 +2x+1) R y−1 5. 3g 3 − g 2 − 13g − 13 7g − 1 2 = (3g + 2) + 2 (7. (y+1) 3 dy 5z 3 −25z 2 +44z−7 R 6.

ex dx = ex + c 15. sec xdx = ln | sec x + tan x| + c x R R 4. kdx = kx + c. sin xdx = − cos x + c −1 x 18. (a > 0. x2 −1 dx 9y 3 −3y+1 R 11. a2dx = a1 tan−1 xa + c R R  8. (any number k) 12. s4 +81 R 8. cot xdx = ln | sin x| + c R R 3. s(s2 +9)2 ds 2θ2 +5θ2 +8θ+4 R 9. xn dx = xn+1 + c. z 3 −z 2 +z−1 dz 8 Basic Integration Formulas The list below shows some basic integration formulas: R R 1. R dx = ln |x| + c 14. tan xdx = ln | sec x| + c n+1 R 2. cos xdx = sin x + c a 19. a 6= 1) R R R 17. ax dx = lna a + c. cosec xdx = − ln |cosec x + cot x| + c R x 16. (θ2 +2θ+2)2 x4 R 10. √adx R  2 −x2 = sin +c R 7. sec2 xdx = tan x + c +x2 . (n 6= −1) 13. cosh xdx = sinh x + c 6. sinh xdx = cosh x + c 5. y 3 −y 2 dy 2z 4 R 12.

.

−1 .

x .

sec x tan xdx = sec x + c a −1 . (a > 0) R 10. √ dx 1 R R 2 9. cosec xdx = − cot x + c 20. 2 x x −a 2 = a sec a +c −1 x 21. √adx R  2 +x2 = sinh + c.

x .

.

.

Weir.net/download/croft_me/student_files/first_aid_kit.D. Integration as Summation. Sec- ond Edition. Inc. cosec x cot xdx = −cosec x + c 2 −a2 = cosh a + c. and Thomas.1.booksites. J. √xdx R R 11. University Calculus: Early Transcendentals. 18 . (2012). (x > a > 0) References 1. M. Engineering Maths First Aid Kit 8.B. Boston. 2. 22. G. Retrieved from www.pdf on the 12th August 2014.. Pearson Education.. Hass.